Acute Toxicity and Early Oncological Outcomes After Intraoperative Electron Radiotherapy (IOERT) as Boost Followed by Whole Breast Irradiation in 157 Early Stage Breast Cancer Patients—First Clinical Results From a Single Center - König, Laila; Lang, Kristin; Heil, Jörg; Golatta, Michael; Major, Gerald; Krug, David; Hörner-Rieber, Juliane; Häfner, Matthias F.; Koerber, Stefan A.; Harrabi, Semi; Bostel, Tilman; Debus, Jürgen; et al. (Frontiers in Oncology, 2019)
Introduction: Breast conserving surgery (BCS) followed by postoperative whole breast irradiation (WBI) is the current standard of care for early stage breast cancer patients. Boost to the tumor bed is recommended for patients with a higher risk of local recurrence and may be applied with different techniques. Intraoperative electron radiotherapy (IOERT) offers several advantages compared to other techniques, like direct visualization of the tumor bed, better skin sparing, less inter- and intrafractional motion, but also radiobiological effects may be beneficial. Objective of this retrospective analysis of IOERT as boost in breast cancer patients was to assess acute toxicity and early oncological outcomes. Material and Methods: All patients, who have been irradiated between 11/2014 and 01/2018 with IOERT during BCS were analyzed. IOERT was applied using the mobile linear accelerator Mobetron® with a total dose of 10 Gy, prescribed to the 90% isodose. After ensured woundhealing, WBI followed with normofractionated or hypofractionated regimens. Patient reports, including diagnostic examinations and toxicity were analyzed after surgery and 6-8 weeks after WBI. Overall survival, distant progression-free survival, in-breast and contralateral breast local progression-free survival were calculated using the Kaplan-Meier method. Furthermore, recurrence patterns were assessed. Results: In total, 157 patients with a median age of 57 years were evaluated. Postoperative adverse events were mild with seroma and hematoma grade 1-2 in 26% and grade 3 in 0.6% of the patients. Wound infections grade 2-3 occurred in 2.2% and wound dehiscence grade 1-2 in 1.9% of the patients. 6-8 weeks after WBI radiotherapy-dependent acute dermatitis grade 1-2 was most common in 90.9% of the patients. Only 4.6% of the patients suffered from dermatitis grade 3. No grade 4 toxicities were documented after surgery or WBI. 2- and 3-year overall survival and distant progression-free survival, were 97.5 and 93.6 %, and 0.7 and 2.8%, respectively. In-breast recurrence and contralateral breast cancer rates after 3 years were 1.9% and 2.8%, respectively. Conclusion: IOERT boost during BCS is a safe treatment option with low acute toxicity. Short-term recurrence rates are comparable to previously published data and emphasize, that IOERT as boost is an effective treatment.